Breast feeding in infants diagnosed with phenylketonuria (PKU): a scoping review - Shalini Ojha; Neil Chadborn; Jahnavi Kalvala; Lydia Chong (BMJ Paediatrics Open, 2023)
Background Phenylketonuria (PKU) is the most common inherited disease of amino acid metabolism, characterised by elevated levels of phenylalanine (Phe). There is a lack of infant feeding guidance for those with PKU. From birth to 6 months of age, breast feeding is the optimal nutrition for an infant and continuing breast feeding for infants with PKU is recommended by European guidelines. However, human breast milk contains Phe in varying quantities, and therefore, the effects breast feeding might have on infants with PKU needs careful consideration.Aim To assess the effects of breast feeding (exclusive or partial) compared with low-Phe formula feeding in infants diagnosed with PKU, on blood Phe levels, growth and neurodevelopmental scores.Methods The Cochrane Inborn Errors of Metabolism Trials Register, MEDLINE and Embase were searched (date of latest search: 9 August 2022). Studies were included if they looked at the effects of breast feeding in infants diagnosed with PKU compared with formula feeding. Predetermined outcomes included blood Phe levels, growth in the first 2 years of life and neurodevelopmental scores.Results Seven observational studies (282 participants) met the inclusion criteria. All studies compared continuation of breast feeding with low-Phe formula versus formula feeding only. While most studies concluded that there was no difference in mean serum Phe levels in their follow-up period, two reported that breastfed infants were more likely to have a normal mean Phe level. Two studies described no difference in mean weight gain after birth, while one found that breastfed infants were more likely to have higher mean weight gain. Two studies commented that breastfed infants achieved higher developmental scores in childhood as compared with formula fed infants.Conclusion Although there are no randomised trials, observational evidence suggests that continuation of breast feeding and supplementation with low-Phe formula is safe and may be beneficial for infants diagnosed with PKU.